The role of autophagy in Graves disease: knowns and unknowns - Hayder M. Al-kuraishy; Ghassan M. Sulaiman; Hamdoon A. Mohammed; Mohammed H. Abu-Alghayth; Salim Albukhaty; Majid S. Jabir; Ali K. Albuhadily; Ali I. Al-Gareeb; Daniel J. Klionsky; Mosleh M. Abomughaid (Frontiers in Cell and Developmental Biology)
Graves disease (GD), an autoimmune disease affects the thyroid gland, results in hyperthyroidisms and goiter. The main cause of GD is not clearly defined; however, stimulating autoantibodies for thyroid stimulating hormone receptor (TSHR) known as thyroid-stimulating immunoglobulins (TSIs) are the primary proposed mechanism. The TSI activation of TSHRs of thyroid gland results in excessive release of thyroid hormones with the subsequent development of hyperthyroidism and goiter. The cellular process of macroautophagy/autophagy is implicated in the pathogenesis of GD and other thyroid diseases. Autophagy plays a critical role in many thyroid diseases and in different stages of the same disease through modulation of immunity and the inflammatory response. In addition, autophagy is also implicated in the pathogenesis of thyroid-associated ophthalmopathy (TAO). However, the exact role of autophagy in GD is not well explained. Therefore, this review discusses how autophagy is intricately involved in the pathogenesis of GD regarding its protective and harmful effects.